2020
DOI: 10.3892/etm.2020.8874
|View full text |Cite
|
Sign up to set email alerts
|

Stomach ‘tastes’ the food and adjusts its emptying: A neurophysiological hypothesis (Review)

Abstract: The presence of taste receptors and their secondary messengers in stomach raised the possibility that the stomach might play a role in food 'tasting' and consequently, it might initiate specific adaptations of its secretory and motor function. Furthermore, activated taste receptors release a variety of chemical mediators able to modulate the activity of the enteric nervous system (ENS), and also to influence both secretory and motor functions of the stomach. Based on the physiological fundamental structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Blended food has a higher viscosity compared to a standard enteral formula and may hence contribute to the reduction in GERD (27) . Taste receptors and endocrine cells located in the gastric mucosa may be activated by different food components of the blends and have a positive effect on secretory and motor functions of the stomach (29) . Lower GI symptoms commonly encountered on standard tube formulas include both diarrhea and constipation ( 27,30 ).…”
Section: Benefits Of a Bdmentioning
confidence: 99%
See 2 more Smart Citations
“…Blended food has a higher viscosity compared to a standard enteral formula and may hence contribute to the reduction in GERD (27) . Taste receptors and endocrine cells located in the gastric mucosa may be activated by different food components of the blends and have a positive effect on secretory and motor functions of the stomach (29) . Lower GI symptoms commonly encountered on standard tube formulas include both diarrhea and constipation ( 27,30 ).…”
Section: Benefits Of a Bdmentioning
confidence: 99%
“…Furthermore, preparation and storage can also impact on the nutrient content of blends, for example, the levels of some vitamins of fruit and vegetable can vary if they are stored fresh compared to frozen (52) . The micronutrient content in blended foods is difficult to measure and could result in deficiencies ( 29,34 ). Mixing blended foods with a prescribed formula or a readily available blended feed or supplement with a stable nutrient content may help to overcome this problem (53) .…”
Section: Nutrient Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…In 'Stomach 'tastes' the food and adjusts its emptying: A neurophysiological hypothesis (Review)', Papacocea et al (10) demonstrated that the presence of taste receptors and their secondary messengers in the stomach raised the possibility that the stomach may play a role in food 'tasting' and consequently, it may initiate specific adaptations of its secretory and motor function. In addition, a variety of chemical mediators are able to modulate the activity of the enteric nervous system (ENS) and to influence both secretory and motor functions of the stomach.…”
mentioning
confidence: 99%